Hybrid green permeable pave with hexagonal modular pavement systems - Rashid M.A.; Abustan I.; Hamzah M.O. (Institute of Physics Publishing, 2023)
Modular permeable pavements are alternatives to the traditional impervious asphalt and concrete pavements. Pervious pore spaces in the surface allow for water to infiltrate into the pavement during rainfall events. As of their ability to allow water to quickly infiltrate through the surface, modular permeable pavements allow for reductions in runoff quantity and peak runoff rates. Even in areas where the underlying soil is not ideal for modular permeable pavements, the installation of under drains has still been shown to reflect these reductions. Modular permeable pavements have been regarded as an effective tool in helping with stormwater control. It also affects the water quality of stormwater runoff. Places using modular permeable pavement has been shown to cause a significant decrease in several heavy metal concentrations as well as suspended solids. Removal rates are dependent upon the material used for the pavers and sub-base material, as well as the surface void space. Most heavy metals are captured in the top layers of the void space fill media. Permeable pavements are now considered an effective BMP for reducing stormwater runoff volume and peak flow. This study examines the extent to which such combined pavement systems are capable of handling load from the vehicles. Experimental investigation were undertaken to quantify the compressive characteristics of the modular. Results shows impressive results of achieving high safety factor for daily life vehicles. Published under licence by IOP Publishing Ltd.